Control of HIF-1α Levels Potentially Promotes the Tissue Repair in Various Conditions Through Target Gene Expression - Riyadh Firdaus; Ani Retno Prijanti (HM Publisher, 2022)
Hypoxia inducible factor-1 (HIF-1) is a transcription factor that plays an important role in maintaining oxygen balance at both the cellular and systemic levels, and is associated with various controls in the body. HIF-1 is a heterodimer of alpha and beta subunits. Alpha subunits are mostly dependent on oxygen levels in the body. In many cancers, excessive HIF-1α is thought to be involved in the promotion of tumor growth and metastasis. In addition, in the induction of systemic hypoxia, there is an increase of HIF-1α in the heart, brain, and even the kidneys as an adaptation response to hypoxia. Several studies regarding HIF-1a expression in traumatic brain injury, found that HIF-1a increased immediately after TBI, and decreased significantly after 24 hours. This can be used as a basis for further research on HIF-1a control as an effort to stop tissue damage or even help tissue repair.